Thrombin generation in patients with COVID-19 with and without thromboprophylaxis - Campello, Elena; Bulato, Cristiana; Spiezia, Luca; Boscolo, Annalisa; Poletto, Francesco; Cola, Marco; Gavasso, Sabrina; Simion, Chiara; Radu, Claudia Maria; Cattelan, Annamaria; Tiberio, Ivo; Vettor, Roberto; et al. (Clinical chemistry and laboratory medicine, 2021)
Thrombin generation (TG) with and without thrombomodulin (TM) was evaluated in COVID-19 patients with different disease severity and thromboprophylaxis regimen, in order to understand the prothrombotic profile. We enrolled consecutive patients with confirmed diagnosis of COVID-19 admitted to Medical Departments (MD) or Intensive Care Units (ICU), and 54 healthy controls. Eighty-nine patients were included (mean age 60.4±16.1 years, 68.5% male); 33.7% admitted to ICU. Twenty-four patients (26.9%) were enrolled before thromboprophylaxis administration; 45 patients (50.6%) received standard and 20 (22.5%) intermediate sub-therapeutic dose thromboprophylaxis. Overall, patients with COVID-19 showed a TG profile comparable to that of healthy subjects (i.e. comparable peak height, endogenous thrombin potential [ETP] with and without TM). The only exception was lag time and time to peak, prolonged in COVID-19 patients vs. controls. MD patients showed a similar TG profile to healthy controls, and ICU patients showed significantly decrease ETP (p=0.030) compared to MD. As for thromboprophylaxis, TG profile was significantly increased in COVID-19 patients without thromboprophylaxis vs. controls and vs. those with thromboprophylaxis. In this latter group, ETP inhibition was significantly decreased (p=0.0003) and positively correlated with anti-Xa activity (r=0.49, p=0.0017). However, patients with thromboprophylaxis had similar TG profile vs. controls. Intermediate dose thromboprophylaxis more effectively inhibited TG in severe COVID-19 patients by increasing ETP inhibition via ETP with TM reduction vs. standard dose. COVID-19 patients showed increased TG at diagnosis. Standard thromboprophylaxis reduced TG to levels of healthy controls. Intermediate sub-therapeutic thromboprophylaxis more effectively inhibited TG by decreasing ETP with TM.